Potensi Daur Ulang Sampah Upacara Adat di Pulau Bali - I Made Wahyu Wijaya; I Kadek Ardi Putra (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
Bali island as one of the best tourism destinations in the world is producing waste around 4.281 ton/day, including the temple waste. Every month, over 3 million Balinese Hindus carry out ceremonies. At the end of the day, each temple produces about 2000 L of temple waste, which is directly disposed to landfill without any treatment due to the insufficiency of waste processing facilities. The treatment of temple waste potentially such as water sanitation, waste accumulation, pollution, and human health. This study describes the characteristic of temple waste generated from home and the efforts of temple waste recycling initiatives. The temple waste is generally composed by 80% of organic material, such as flowers, leaves, fruit and food waste, coconut, bamboo, and in other side the plastic does exist. Some initiatives in recycling the temple waste were done in the previous research, such as aromatherapeutic incense from discarded flowers, generating vermicompost by mixing the discarded flowers with cow dung, and producing biofuel from marigold flowers. A recycling improvement is urgently needed by the existing temple waste in Bali. It is expected that Balinese Temple as the cultural icon of Bali would not be longer become the waste contributor to the landfill.